Physical Activity Educational Model Program to Lower Blood Glucose in Parung Ponteng - Novia Wulansari; Wasis Widodo; Desinta Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this community service is to introduce the importance of physical activity using a community empowerment-based educational model to control blood glucose, especially in DM patients. The results of community service show that educational methods followed by physical activity practices can increase knowledge about the importance of physical activity in lowering blood glucose. Health education is carried out for people who suffer from DM and the general public. The conclusion of this community service is an educational model of community-based physical activity programs in the form of group discussions and direct practice of physical activity can increase knowledge about the importance of controlling blood glucose. Suggestions, the government and educational institutions need to increase preventive and promotive efforts to increase physical activity behavior in an effort to control DM in the Parung Ponteng area, Bogor Regency.